Terminologia da indústria de artefatos de borracha: proposta de um vocabulário - Bazzon, Solange Cristina Maida (2009)
The rubber industry is a sector that contributes significantly with the national economy due to the fact that it is part of a wide range of products. Therefore, we verified the need of a terminological systematization in this field. Based on this fact, our objective is to elaborate a monolingual vocabulary (glossary) of rubber goods in the automotive sector, with English equivalences. This paper is supported by the Communicative Terminology Theory proposed by Maria Tereza Cabré. Under a communicative perspective, the methodology of this research contemplated the compilation of a corpus as well as the utilization of a computer tool, the Unitex, in order to manage the texts that make part of this corpus. We extracted words (semi automatically) which we considered a term candidate, inserted them in the ontology, elaborated and filled out the terminology forms which were used as a term dossier; elaborated a text definition basis which was constantly fed with new information and sequentially we wrote the definitions. The definition texts of the rubber vocabulary (glossary) are based on the researches at Terminology Group Studies department GETerm. The microstructure - headword - contemplates systematic (obligatory) and asystematic (non obligatory) information that facilitates the peoples use. Concerning the vocabulary/ glossary microstructure we followed the TERMICAT s (1990) proposal, which aims the specialized communication.